Analisis Dampak Kebijakan Stimulus Covid–19 melalui Restrukturisasi Kredit pada Permodalan dan Likuiditas Perbankan dan BPR - emilda emilda; Meilin Veronica (Jurnal Ilmiah Ekonomi Global Masa Kini, 2023)
The new variant of COVID-19, namely the delta variant, has made the impact of the coronavirus disease 2019 (COVID 19) pandemic continue. Government policies that are still implementing Community Activity Restrictions (PPKM) have resulted in several business actors and employees experiencing a decline and even losing their income during the Covid-19 pandemic. The issuance of the POJK is an anticipatory and follow-up measure against a potential decrease in the debtor's capacity to pay debts to the bank. As a form of this anticipatory and follow-up effort, the Financial Services Authority (OJK) extended the term of the bank credit restructuring policy from March 2022 to March 2023. Credit restructuring is an effort to improve credit activities for debtors who have the potential to experience difficulties in fulfilling their obligations. If the term of the credit/financing restructuring agreement expires before March 31, 2023, then the credit/financing can be determined as having the quality of Current to. end of the term of the restructuring agreement. Credit restructuring will indeed maintain the quality of banking assets. This is because restructured loans will automatically run smoothly. However, the restructuring costs will add to the bank's burden and could disrupt bank capital and liquidity. Based on the results of the analysis, the capital and liquidity levels of Commercial Banks, Conventional Commercial Banks (BUK), and Rural Banks are still adequate and very good, This can be seen from the great value of the CAR and LDR ratio amid increasing credit risk and decreasing profitability in line with economic activity who have not recovered as a result of the conditions of the Covid-19 pandemic.Keywords: Covid - 19 stimulus policy, credit restructuring, capital, liquidity, banking and Rural Banks